2017
DOI: 10.1787/a8e751b7-en
|View full text |Cite
|
Sign up to set email alerts
|

Can potential mismeasurement of the digital economy explain the post-crisis slowdown in GDP and productivity growth?

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
(14 reference statements)
0
23
0
1
Order By: Relevance
“…However, these gains from digitalisation have not yet materialised, with productivity growth in most of the world having been relatively subdued since the 2008 financial crisis or even prior to this, raising a number of open questions, regarding potential lagged effects of these new technologies, structural versus cyclical factors and, of course, measurement. While a growing body of evidence suggests that measurement, or rather "mis-measurement", is not the primary cause (Syverson, 2016;Byrne, Fernald and Reinsdorf, 2016;Ahmad et al, 2017;Reinsdorf and Schreyer, 2019), many challenges remain in the practical measurement of the digital economy, including its inclusion in both GDP and productivity.…”
Section: Measuring the Digital Economymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these gains from digitalisation have not yet materialised, with productivity growth in most of the world having been relatively subdued since the 2008 financial crisis or even prior to this, raising a number of open questions, regarding potential lagged effects of these new technologies, structural versus cyclical factors and, of course, measurement. While a growing body of evidence suggests that measurement, or rather "mis-measurement", is not the primary cause (Syverson, 2016;Byrne, Fernald and Reinsdorf, 2016;Ahmad et al, 2017;Reinsdorf and Schreyer, 2019), many challenges remain in the practical measurement of the digital economy, including its inclusion in both GDP and productivity.…”
Section: Measuring the Digital Economymentioning
confidence: 99%
“…Exactly the same accounting treatment is applied to radio and TV service providers. While the national accounts community is currently discussing the potential to treat (part of) the output of these service providers as final rather than intermediate consumption, the limited size of advertising services in GDP means the resulting effect on the value of output is expected to be small (Byrne et al, 2016;Ahmad et al, 2017).…”
Section: Measuring the Digital Economymentioning
confidence: 99%
“…At the international level, measurement errors have been put forward as a possible explanation, but overall their impact remains limited (Byrne, Fernald and Reinsdorf, 2016;Syverson 2017, Ahmad, Ribarsky andReinsdorf, 2017). In the same vein, reallocation from high to low-productive sectors is also estimated to have played a marginal role (Barnett et al, 2014;Kierzenkowski et al, 2018;Riley, Rincon-Aznar and Samek, 2018;Sorbe et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Syverson (2017) concluded that mismeasurement is unlikely to be explanation for the productivity slowdown. Ahmad, Ribarsky and Reinsdorf (2017) developed alternative price and welfare measures for several items and found relatively small impacts on GDP growth. Byrne, Fernald and Reinsdorf (2016) found that the mismeasurement of US productivity is small compared to the magnitude of the productivity slowdown and did not grow when productivity slowed.…”
mentioning
confidence: 99%